Crosslinking mechanism of supramolecular elastomers based on linear bifunctional polydimethylsiloxane oligomers. Issue 18 (18th January 2016) - You, Yang; Zhang, Anqiang; Lin, Yaling
ABSTRACT: Supramolecular elastomers (SESis) were synthesized via a simplified synthesis route on the basis of a linear bifunctional polydimethylsiloxane. Compared with previous synthesis methods, the structure of the product was much clearer. The 1 H‐NMR titration results show that the hydrogen‐bond associations in SESis were relatively weak. During 1 H‐NMR reaction monitoring, the viscosity analysis of SESis and the model reactions demonstrated a previously neglected covalent crosslinking reaction not only during the reaction process but also during the postprocess; this led to a hybrid network, that is, covalent crosslinking and hydrogen association, in SESis. This finding explained the poor solubility of the SESis, and it provides us with an important way to controllably synthesize this material and adjust its properties. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43385. Abstract :